2021
DOI: 10.3390/s21020572
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Neural Plasticity Using a Low-Cost Open Source Brain-Computer Interface and a 3D-Printed Wrist Exoskeleton

Abstract: Brain-computer interfaces (BCIs) have been proven to be useful for stroke rehabilitation, but there are a number of factors that impede the use of this technology in rehabilitation clinics and in home-use, the major factors including the usability and costs of the BCI system. The aims of this study were to develop a cheap 3D-printed wrist exoskeleton that can be controlled by a cheap open source BCI (OpenViBE), and to determine if training with such a setup could induce neural plasticity. Eleven healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…Он представляет собой комплекс устройств, которые регистрируют и распознают биоэлектрическую активность мозга, возникающую в ответ на намерение осуществить какое-либо действие, а затем трансформируют ее в сигналы биологической обратной связи или команды управления внешними устройствами -в частности, экзоскелетом. При всей кажущейся сложности уже есть исследования, показавшие, что с помощью недорогих электроэнцефалографов можно регистрировать электрическую активность моторной коры, а экзоскелет -напечатать на 3D-принтере, что не сопряжено со значительными материальными затратами [24].…”
Section: современные перспективные методы физической реабилитацииunclassified
“…Он представляет собой комплекс устройств, которые регистрируют и распознают биоэлектрическую активность мозга, возникающую в ответ на намерение осуществить какое-либо действие, а затем трансформируют ее в сигналы биологической обратной связи или команды управления внешними устройствами -в частности, экзоскелетом. При всей кажущейся сложности уже есть исследования, показавшие, что с помощью недорогих электроэнцефалографов можно регистрировать электрическую активность моторной коры, а экзоскелет -напечатать на 3D-принтере, что не сопряжено со значительными материальными затратами [24].…”
Section: современные перспективные методы физической реабилитацииunclassified
“…Different paradigms have been used in BCI applications based on EEG for robot control, such as Motor Imagery (MI) [19,[27][28][29][30][31][32][33], P300 evoked potentials [14,34,35], or Steady-State Visually Evoked Potentials (SSVEP) [36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Openvibe has been used for multiple applications and with different types of paradigms such as motor imagination to control a robotic arm or a robotic hand [30,31], motor imagination in neural plasticity with a wrist exoskeleton [32], with the P300 paradigm for the control of an electric chair [23], P300 for the control of a manipulator robot [35], surface electromyographic signals for the control of a functional electrical stimulator (FES) [82], neurorehabilitation [28,33,83], music [84], mobile robots [85] or processing with motor imagination or P300 [86][87][88][89] with different amplifiers [90].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the numerous studies focused on the investigation of the neurophysiological effects induced by the MI-based BCI, little is known about how adding the feedback to BCI training influences cortical excitability. However, it was shown that increased motor cortex excitability during MI BCI-based NF training can promote the plasticity in motor cortical areas, which opens up a wide range of neurorehabilitation therapy technologies [53,54]. In our previous research, we proposed the BCI paradigm employing only a vibrotactile channelwithout the use of visual control elements (with the eyes closed) [19].…”
Section: Introductionmentioning
confidence: 99%